Dynamics of a discrete predator-prey system with nonconstant death rate (2017)
In this paper, we will consider a discrete non-autonomous predator-prey system with nonconstant death rate. We give sufficient conditions in order to get a dissipative and permanent system. By using the continuation theorem based on Gaines and Mawhin's coincidence degree, we study the existence of positive periodic solutions when the coecients of system are periodic. A numerical example is given to illustrate the effectiveness of the main result.